Regulatory Gap Versus Performance Reality: Thermal Assessment of a Social Housing Module in the Peruvian Andes - Palomino-Olivera, E.; Ancco-Peralta, M.; Salas Velásquez, V.; Mejia-Solis, E.; Gudiel Rodríguez, E. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
In high-altitude regions of the Global South, social housing programs are essential for mitigating vulnerability to low temperatures, but their standardized designs often fail to meet thermal performance codes. This study evaluates a “Sumaq Wasi” adobe housing module in the Peruvian Andes (Kunturkanki, 4237 m a.s.l.) during the 2023 frost season. We comparatively applied the 2014 and 2022 draft versions of the Peruvian standard EM.110 to assess the building envelope’s thermal transmittance and condensation risk, benchmarking monitored indoor temperatures against adaptive comfort models. The results revealed widespread non-compliance with thermal transmittance limits, especially for the roof and floor, although condensation risk was low. While indoor temperatures failed to meet conventional standards, they aligned with regionally adapted comfort ranges. We conclude that the standardized module design is insufficient for local climatic demands and argue that social housing policies must evolve, balancing regulatory stringency with context-aware bioclimatic design to be effective.
Keywords: Benchmarking; Adobe; Public housing; Thermal transmittance; Vulnerability (computing); Thermal comfort; Social vulnerability; Built environment; https://purl.org/pe-repo/ocde/ford#2.01.04